Comparison of Aedes aegypti arbovirus transmission thresholds in two communities with differing water supply infrastructure - Claudia Maria Romero-Vivas; Dhay Potes; Pedro José Arango-Padilla; Clara Eugenia Roa-García; Andrew Keith Falconar (BMC, 2024)
Abstract Background To assess whether the 'economic boom' in the tropical seaport city of Barranquilla improved tapped water supplies to socio-economically poor neighbourhoods resulting in: (1) their reduced use for domestic water-storage in large (> 1,000-litre) custom-made cement tanks which are their principal Aedes aegypti breeding sites and (2) their pupae/person index (PPI) values to below their established 0.5-1.5 PPI arbovirus transmission-threshold value, compared to matched neighbourhoods in the: (a) pre-economic boom (2004) period in Barranquilla and (b) economically-neglected seaport city of Buenaventura. Methods The simple, accurate and robust water surface sweep-net/calibration factor or total count methods were used to determine the total Ae. aegypti pupae numbers in greater or less than 20-litre water-holding container types located 'inside' or 'outside' these neighbourhood premises. The women residents also participated in questionnaire-based responses about their domestic water supplies, water-storage and maintenance and mosquito life stages and disease transmission knowledge, to subsequently plan appropriate resident education programmes. Microsoft Excel 8.0 with OpenEpi was used to determine the samples sizes and the statistical values. Results Tapped water supplies to the three poor Barranquilla neighbourhoods were dramatically increased from 2004 to 2023 resulting in their residents significantly reducing their: (a) large cement water-storage tanks from 1 per 6.9 (2004) to 1 per 31.2 (2020) premises (z = 10.5: p = 0) and (b) PPI values to 0.16, 0.19 and 0.53 (mean: 0.29: 95% CI ± 0.4) in each study neighbourhood. In contrast, tapped water supplies remained inadequate in the Buenaventura neighborhoods, thereby resulting in their continued use of many large (> 1,000-litre) water-storage containers (Barranquilla: 1 per 31.2 and Buenaventura: 1 per 1.5 premises: z = − 9.26: p = 0), with unacceptably high 0.81, 0.88 and 0.99 PPI values in each study neighbourhood (mean 0.89: 95% CI ± 0.12). Conclusions Improved tapped water supplies resulted in reduced numbers of large custom-made stoneware water-containers, as are employed by poor residents throughout the world, as well as their Ae. aegypti PPI transmission threshold values which, together with appropriate residents' education programmes, are also urgently to reduce to prevent/reduce Ae. aegypti transmitted human diseases globally.